2021
DOI: 10.1088/1361-6463/ac34ac
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on collision-coalescence of droplets under the synergistic effect of charge and sound waves: orthogonal design optimization

Abstract: As an efficient approach to improve visibility, defogging technology is essential for the operation of ports and airports. This paper proposes a new and hybrid defogging technology, i.e. an electric–acoustic defogging method. Specifically, the droplets are charged by corona discharge, which is beneficial to overcome the hydrodynamic interaction force to improve the droplet collision efficiency. Meanwhile, sound waves (especially acoustic turbulence) promote the relative movement of droplets to increase the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…To further enhance the discharge current by increasing the number of micro-nano protrusions is a spontaneous idea. However, the results in table 3 show that the discharge current under the barbed wire with two protrusions is only slightly higher (less than 9%) than that with only one protrusion (type [5][6][7][8][9][10][11]. To further study the underlying mechanism, the electric field intensity and local charge density at 2.5 mm above the ground electrode are extracted and plotted in figures 8(b) and (c), respectively.…”
Section: Fog Harvesting Efficiency Vs Micro-nano Protrusion Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…To further enhance the discharge current by increasing the number of micro-nano protrusions is a spontaneous idea. However, the results in table 3 show that the discharge current under the barbed wire with two protrusions is only slightly higher (less than 9%) than that with only one protrusion (type [5][6][7][8][9][10][11]. To further study the underlying mechanism, the electric field intensity and local charge density at 2.5 mm above the ground electrode are extracted and plotted in figures 8(b) and (c), respectively.…”
Section: Fog Harvesting Efficiency Vs Micro-nano Protrusion Parametersmentioning
confidence: 99%
“…Several field trials carried out in Oman [2], the Philippines [3], California [4] and others have confirmed the feasibility of fog harvesting. To enhance fog collection, researchers have proposed a variety of multi-functional methods, such as biomimetic surfaces from plants and animals [5,6], multi-layer harvesters [7,8], acoustic-induced droplet collision-coalescence [9,10], surface chemistry wettability [11][12][13] and electrostatic fog harvesting [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…For 40-100 Hz acoustic intervention on microdroplets, Bai et al (2020); Bai et al (2021a); Bai et al (2021b) found that the particle size increment was significantly affected by the sound frequency, and the droplets isotope values increased after interference of acoustics. He et al (2021) conducted experiments on droplets by combined sound waves of 200-600 Hz and electric field. The effects of sound wave and electricity on droplet agglomeration have been proved, and the optimal sound frequency was 400 Hz.…”
Section: Introductionmentioning
confidence: 99%